2006
DOI: 10.1063/1.2213180
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic anisotropy of wear on a polycrystalline diamond surface

Abstract: We correlate topography and diffraction measurements to demonstrate that grain orientation profoundly influences polishing rates in polycrystalline diamond synthesized by chemical vapor deposition. Grains oriented with {111} or {100} planes perpendicular to the surface normal polish at significantly lower rates compared with grains of all other orientations when the surface is polished in continuously varying in-plane directions. These observations agree with predictions of the periodic bond chain vector model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 14 publications
(13 reference statements)
1
17
0
Order By: Relevance
“…They suggested that the high wear resistance of NPD is attributed to the extremely strong binding nature of the constituent nanocrystals and the presence of a number of grains with {111} planes facing to the surface. Indeed, a careful abrasion test conducted using CVDgrown micropolycrystalline diamond by El-dasher et al, [19] demonstrated super wear resistance of {111} planes. Since our new nanolayered diamond has top surfaces which are terminated exclusively by {111} due to the strong preferred orientation of individual crystals, it is expected to provide significantly higher antiwear performance.…”
Section: Resultsmentioning
confidence: 99%
“…They suggested that the high wear resistance of NPD is attributed to the extremely strong binding nature of the constituent nanocrystals and the presence of a number of grains with {111} planes facing to the surface. Indeed, a careful abrasion test conducted using CVDgrown micropolycrystalline diamond by El-dasher et al, [19] demonstrated super wear resistance of {111} planes. Since our new nanolayered diamond has top surfaces which are terminated exclusively by {111} due to the strong preferred orientation of individual crystals, it is expected to provide significantly higher antiwear performance.…”
Section: Resultsmentioning
confidence: 99%
“…However, analyzing molecules in harsh conditions such as extreme temperatures, voltages or pH conditions could lead to the malfunctioning or in extreme cases to the destruction of the chips with conventional membranes. The problem can be solved by establishing nanopores in diamond since this material possesses exceptional physio-chemical properties such as the highest hardness and Young's modulus (1200 GPa) of all known solids, a very high thermal conductivity (20)(21)(22) W cm −1 K −1 ) and a low thermal expansion coefficient [9], [10], [11], [12]. Furthermore, because of its wide band gap, the electrochemical potential window of diamond is significantly larger and the background current within this regime considerably lower than conventional electrodes made from metals or graphite [13].…”
Section: Introductionmentioning
confidence: 99%
“…Diamond is the perfect candidate for this task since it has exceptional properties such as the highest hardness and Young's modulus ͑1200 GPa͒ of all known solids, a very high thermal conductivity ͑20-22 W cm −1 K −1 ͒ and a low thermal expansion coefficient. [4][5][6][7] It can be used to attach binding sites in order to be able to detect specific molecules. 8 Furthermore due to its wide band gap, it is well known, that the background current of diamond is very low and the potential window very wide compared to conventional electrodes made from metals or graphite.…”
mentioning
confidence: 99%